The Influence of Hospital Health Promotion Standards on the Implementation of PKRS at Idaman Regional Hospital Banjarbaru - Liana Fitriani Hasymi; Muhammad Rizky Firzatullah; Muhammad Hadarani; Eny Hastuti (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2026)
Background: Health promotion is a hospital institution's effort to ensure the fulfillment of the public's right to obtain health-related information and education, particularly within the hospital environment, and to ensure the provision of holistic, effective, efficient, integrated, and sustainable health services. Objective: This study aims to examine the determinants impacting the implementation of health promotion programs at Idaman Hospital in Banjarbaru. Design: This study used a quantitative approach with a cross-sectional design. The sample consisted of 156 respondents selected using probability sampling techniques. Data analysis was performed using chi-square tests and logistic regression to identify determinants of hospital health promotion (PKRS) implementation. Results: The analysis revealed a significant relationship between PKRS implementation and regulations (p=0.003), assessment (p=0.004), intervention (p=0.008), and monitoring and evaluation (p=0.001). Logistic regression analysis revealed that the most dominant factor was monitoring-evaluation with a p-value of 0.003 and an odds ratio [Exp(B)] of 5.421, indicating that PKRS implementing units were 5.4 times more likely to succeed when implementing a continuous evaluation system. These findings recommend strengthening the evidence-based clinical audit system, human resource capacity through tiered training, and integrating the PKRS program into the hospital's strategic plan.